Media's Role in the Making of a Democrat: Evidence from East Germany - Tim Friehe; Helge Müller; Florian Neumeier (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper explores the causal influence of media content on voting behavior. We exploit a natural experiment involving access to West German TV within the German Democratic Republic. Focusing on federal and state election outcomes in the post-reunification decade (i.e., a time at which TV content was harmonized), we find that municipalities that had access to Western TV broadcasts before reunification have lower vote shares for left-wing and right-wing extremist parties. With regard to potential channels, we provide evidence based on survey data that GDR citizens with access to West German TV were less loyal to the socialist regime, less hostile toward foreigners, and exhibited higher levels of social capital. Our findings thus support the notion that access to free media influences political attitudes and facilitates the consolidation of democracy.
Keywords: D72; L82; P30; 330; voting; extremism; television; media; natural experiment; Germany